A modified flexible GnRH antagonist protocol using antagonist early cessation and a gonadotropin step-down approach improves live birth rates in fresh cycles: a randomized controlled trial - Xu, Bei; Geerts, Dirk; Yuan, Jiaying; Wang, Mengting; Li, Zhou; Lai, Qiaohong; Zheng, Yu; Liu, Si; Yang, Shulin; Zhu, Guijin; Jin, Lei (Human reproduction (Oxford), 2024)
Abstract STUDY QUESTION Can pregnancy outcomes following fresh elective single embryo transfer (eSET) in gonadotropin-releasing hormone (GnRH) antagonist protocols increase using a gonadotropin (Gn) step-down approach with cessation of GnRH antagonist on the day of hCG administration (hCG day) in patients with normal ovarian response? SUMMARY ANSWER The modified GnRH antagonist protocol using the Gn step-down approach and cessation of GnRH antagonist on the hCG day is effective in improving live birth rates (LBRs) per fresh eSET cycle. WHAT IS KNOWN ALREADY Currently, there is no consensus on optimal GnRH antagonist regimens. Studies have shown that fresh GnRH antagonist cycles result in poorer pregnancy outcomes than the long GnRH agonist (GnRHa) protocol. Endometrial receptivity is a key factor that contributes to this phenomenon. STUDY DESIGN, SIZE, DURATION An open label randomized controlled trial (RCT) was performed between November 2021 and August 2022. There were 546 patients allocated to either the modified GnRH antagonist or the conventional antagonist protocol at a 1:1 ratio. PARTICIPANTS/MATERIALS, SETTING, METHODS Both IVF and ICSI cycles were included, and the sperm samples used were either fresh or frozen from the partner, or from frozen donor ejaculates. The primary outcome was the LBRs per fresh SET cycle. Secondary outcomes included rates of implantation, clinical and ongoing pregnancy, miscarriage, and ovarian hyperstimulation syndrome (OHSS), as well as clinical outcomes of ovarian stimulation. MAIN RESULTS AND THE ROLE OF CHANCE Baseline demographic features were not significantly different between the two ovarian stimulation groups. However, in the intention-to-treat (ITT) population, the LBRs in the modified antagonist group were significantly higher than in the conventional group (38.1% [104/273] vs. 27.5% [75/273], relative risk 1.39 [95% CI, 1.09–1.77], P = 0.008). Using a per-protocol (PP) analysis which included all the patients who received an embryo transfer, the LBRs in the modified antagonist group were also significantly higher than in the conventional group (48.6% [103/212] vs. 36.8% [74/201], relative risk 1.32 [95% CI, 1.05–1.66], P = 0.016). The modified antagonist group achieved significantly higher implantation rates, and clinical and ongoing pregnancy rates than the conventional group in both the ITT and PP analyses (P < 0.05). The two groups did not show significant differences between the number of oocytes retrieved or mature oocytes, two-pronuclear zygote (2PN) rates, the number of embryos obtained, blastocyst progression and good-quality embryo rates, early miscarriage rates, or OHSS incidence rates (P > 0.05). LIMITATIONS, REASONS FOR CAUTION A limitation of our study was that the subjects were not blinded to the treatment allocation in the RCT trial. Only women under 40 years of age who had a good prognosis were included in the analysis. Therefore, use of the modified antagonist protocol in older patients with a low ovarian reserve remains to be investigated. In addition, the sample size for Day 5 elective SET was small, so larger trials will be required to strengthen these findings. WIDER IMPLICATIONS OF THE FINDINGS The modified GnRH antagonist protocol using the Gn step-down approach and cessation of GnRH antagonist on hCG day improved the LBRs per fresh eSET cycle in normal responders. STUDY FUNDING/COMPETING INTEREST(S) This project was funded by grant 2022YFC2702503 from the National Key Research & Development Program of China and grant 2021140 from the Beijing Health Promotion Association. The authors declare no conflicts of interest. TRIAL REGISTRATION NUMBER The RCT was registered in the Chinese Clinical Trial Registry; Study Number: ChiCTR2100053453. TRIAL REGISTRATION DATE 21 November 2021. DATE OF FIRST PATIENT’S ENROLLMENT 23 November 2021